ANALISIS KINERJA SIMPANG EMPAT TAK BERSINYAL (Studi Kasus : Persimpangan Jalan Ahmad Yani Ekor Lubuk Kota Padang Panjang). - Hendri .S Hendri .S; Ishak Ishak; Selpa Dewi (Ensiklopedia Research and Community Service Review, 2021)
ABSTRACTTransportation is the movement of people or goods from one place to another or from the place of origin to the destination with or without the use of assistive devices. To expedite these activities, it is necessary to increase the capacity of the road structure where adequate planning of transportation modes is needed by prioritizing aspects of speed and also considering aspects of safety, comfort and environmental impact. To optimize the function of the road network, an intersection transportation system is implemented. The Ahmad Yani Street intersection (Padang Panjang – Solok Highway) is one of the main roads in the city of Padang Panjang where the activity in this road area is quite large. The pattern of traffic regulation at this intersection is not yet regular, so vehicles are often found scrambling for space to pass through the intersection and have a higher risk of accidents, this will cause congestion. The purpose of this study is to determine the level of performance of unsignaled intersections in serving traffic based on data obtained from field surveys and to determine the traffic flow at the Ahmad Yani, Street, Padang Panjang City. The research method used in this research is quantitative (field survey). The survey was conducted for 3 days, namely Monday, Friday, and Saturday. Which from the presearch results peak hours occur on Mondays. This intersection has a high side resistance with a degree of saturation (DS) = 1.883, the average delay is -9.52 and the queue probability is also high 160.29% - 379.51%.Keywords : Degree of Saturation, Side Barrier, Unsignalized Intersection, Delay, Queue Opportunity, MKJI